Experience rates of low-carbon domestic heating technologies in the United Kingdom. (September 2021) - Renaldi, Renaldi; Hall, Richard; Jamasb, Tooraj; Roskilly, Anthony P.
Abstract: This paper presents the experience curves of low-carbon domestic heating technologies in the United Kingdom between 2010 and 2019. The deployment of these technologies has been acknowledged as one of the main actions toward decarbonising the heating sector. In the UK, several deployment oriented policies have been implemented, such as the Renewable Heat Incentive (RHI). In this study, we focus on the following domestic heating technologies: air-source heat pumps, ground-source heat pumps, solar thermal collectors, and biomass boilers. Condensing combination gas boilers are also included to act as the baseline/incumbent technology. Using UK installation cost data for 2010 to 2019, we found that low-carbon heating technologies had experience rates of; air-source heat pumps −2.3 ± 5%, ground-source heat pumps −0.8 ± 4%, biomass boilers 0.1 ± 2%, and solar thermal 13 ± 5%, all significantly lower than the reported rates of similar technologies in the literature. Furthermore, we found that gas boilers have potentially reached the floor price at approximately £30/kW. The resulting experience rates can be used in energy economics models and to inform policymakers in developing further deployment programs. Highlights: Experience rates of low-carbon heating technologies in the UK are relatively low. Installation costs of heat pumps and biomass are not showing decreasing trends. The price of condensing gas boilers has potentially arrived at the floor price of 30 £/kW. Significant variation of rates between different countries for the same technology.